2005
DOI: 10.1159/000086906
|View full text |Cite
|
Sign up to set email alerts
|

Somatic chromosomal abnormalities in infertile men and women

Abstract: Infertility – the inability to achieve conception or sustain a pregnancy through to live birth – is very common and affects about 15% of couples. While chromosomal or genetic abnormalities associated with azoospermia, severe oligozoospermia or primary ovarian failure were of no importance for reproduction prior to the era of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), advances in assisted reproductive techniques (ART) now enable many infertile couples to have children. These devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 281 publications
(163 reference statements)
5
81
0
4
Order By: Relevance
“…Genetic causes must be sought by systematic evaluation of infertile men and affected couples informed about the implications of such diagnoses for assisted reproductive technology outcome and their potential offspring. An association between human male infertility and chromosomal anomalies has been known for a long time [56,57]. The incidence of karyotype abnormalities among patients with infertility has been reported to range between 2% to 21%, being low among azoospermic men [58][59][60].…”
Section: Molecular Insight Into Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic causes must be sought by systematic evaluation of infertile men and affected couples informed about the implications of such diagnoses for assisted reproductive technology outcome and their potential offspring. An association between human male infertility and chromosomal anomalies has been known for a long time [56,57]. The incidence of karyotype abnormalities among patients with infertility has been reported to range between 2% to 21%, being low among azoospermic men [58][59][60].…”
Section: Molecular Insight Into Male Infertilitymentioning
confidence: 99%
“…The possible association between chromosomal abnormalities and male infertility became evident following the result of the first large karyotype survey involving subfertile males [56,61]. The Y chromosome in mammals carries the gene that switches the development of the indifferent gonad from the default female pathway to the male pathway and results in the development of the testis [62].…”
Section: Molecular Insight Into Male Infertilitymentioning
confidence: 99%
“…(ii) It has also been suggested that any kind of chromosomal aberration can reduce the ability of correct chromosomal pairing during meiosis I (1), which can cause fertility problems especially in males (17). (iii) There are indications that OAT/oligozoospermia is significantly correlated with sSMC presence (7%), while azoospermia and sSMC are correlated in <1% of the corresponding cases (18 Fig. 3); in these cases uniparental disomy (UPD) of the sister chromosomes might be a possible explanation, even though such UPD was up to now only proven for de novo sSMC cases.…”
Section: Fertility Problems In Ssmc Carriers and Evolutionary Effectsmentioning
confidence: 99%
“…Based on this last classification criterion, CCR can be divided into three-way rearrangements (when three chromosomes suffer one break each and interchange the distal segments), exceptional CCR (when more than one breakpoint per chromosome is present), and double two-way translocations (involving two or three independent translocations in the same carrier). Despite the lack of surveys referring to a concrete incidence in the general population, the frequency among infertile individuals has been estimated around 0.1 % [14].…”
Section: Introductionmentioning
confidence: 99%